MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA MELALUI PENGEMBANGAN ALAT PERAGA GAYA LORENTZ [IMPROVING STUDENTS’ COGNITIVE LEARNING OUTCOMES THROUGH DEVELOPMENT OF LORENTZ FORCE TOOLS] - Lia Sianipar; Sunaryo Sunaryo; I Made Astra (Universitas Pelita Harapan, 2020)
Based on the results of the distribution of questionnaires to students and interviews with physics teachers, there are two things that the author found. The first is students still have difficulty in determining the direction of Lorentz force and the second is the availibility of tools for Lorentz force practicums at school is still a separate component. So, it is necessary to develop Lorentz force media that can overcome both problems. The purpose of this study is to improve students' cognition through developing Lorentz force tools. The research and development (R&D) of the Borg and Gall model is the methodology applied in this study. The research instrument used was the test instrument. The results of the development of tools is validated by material experts, media experts, and Physics teachers. The validity of the Lorentz force tools is calculated using the product moment formula, reliability is calculated using the KR-20 formula. The results of data analysis in the experimental class, obtained an average score of pretest of 29.17, grooming post-test average of 82.78. From these data, it can be concluded that the development of Lorentz force tools can improve students’ learning outcomes in the cognitive aspect.BAHASA INDONESIA ABSTRACT: Berdasarkan dari hasil penyebaran angket kepada siswa dan wawancara terhadap guru Fisika ada dua hal yang penulis temukan. Pertama masih ditemukan siswa yang kesulitan dalam menentukan arah gaya Lorentz dan yang kedua KIT praktikum gaya Lorentz yang tersedia di sekolah masih dalam komponen yang terpisah. Sehingga perlu adanya pengembangan media gaya Lorentz yang dapat mengatasi kedua permasalahan tersebut. Tujuan dari penelitian ini adalah untuk meningkatkan kognitif siswa melalui pengembangan alat peraga gaya Lorentz. Penelitian dan pengembangan (R & D) model Borg and Gall merupakan metodologi yang diterapkan pada penelitian ini. Instrumen penelitian yang digunakan instrumen tes. Hasil pengembangan alat peraga divalidasi oleh ahli materi, ahli media dan guru Fisika. Validitas alat peraga gaya Lorentz dihitung dengan menggunakan rumus product Moment, reliabilitas dihitung dengan menggunakan rumus KR-20. Hasil dari analisis data pada kelas eksperimen, diperoleh skor rata-rata pre-test sebesar 29,17, dan rata-rata post-test82,78. Dari data tersebut dapat simpulkan melalui pengembangan alat peraga gaya Lorentz mampu meningkatkan hasil belajar siswa pada ranah kognitif.